Metode pembelajaran eklektik bahasa Arab di Pondok Pesantren Nurul Ulum Malang - Sumiati, Sumiati (Maliki Interdisciplinary Journal, 2023)
This research aims to describe the eclectic Arabic learning method and its implementation in Arabic language learning as well as the advantages and disadvantages of implementing it. The results of the research show that the concept of an eclectic learning method is a combined method or mixed method which essentially has several names, namely: thariqah Mukhtarah, thariqah Taulifiyah, thoriqah Intiqa’iyyah, and thariqah Mudzawijah. This method emerged as a form of a combination of previously existing methods. Implementation of the eclectic method of eclectic learning methods for Arabic at the Nurul Ulum Malang Islamic Boarding School, namely by (1) learning activities that have carried out eclectic learning in the form of oval practice, reading aloud, and questions and answers. (2) Language skills are taught in the order of speaking, writing, reading, and understanding. (3) In this method there is also practice translating grammar lessons deductively. (4) used tools or audio-visual characteristics. The advantage of the Eclectic Learning Method is that this method is a complementary method to previous methods. Learning is more effective, interesting, and varied. The disadvantage of the Eclectic Learning Method is the limited time used to apply this method.